Synthesis of a Non-Symmetrical Disorazole C1-Analogue and Its Biological Activity - Luca Lizzadro; Oliver Spieß; Silke Reinecke; Marc Stadler; Dieter Schinzer (Molecules, 2024)
The synthesis of a novel disorazole C1 analogue is described, and its biological activity as a cytotoxic compound is reported. Based on our convergent and flexible route to the disorazole core, we wish to report a robust strategy to synthesize a non-symmetrical disorazole in which we couple one half of the molecule containing the naturally occurring oxazole heterocycle and the second half of the disorazole macrocycle containing a thiazole heterocycle. This resulted in a very unusual non-symmetrical disorazole C1 analogue containing two different heterocycles, and its biological activity was studied. This provided exciting information about SAR (structure-activity-relationship) for this highly potent class of antitumor compounds.